Amphibians of the Maldives Archipelago - Das, Indraneil (Natural History Publications (Borneo) Sdn. Bhd, 2014)
The Maldive archipelago lies between latitudes 8°N and 1°S and longitudes 72–74°E, and extends for 756 km southwest of peninsular India (Fig. 1). The archipelago is composed of interrupted double chains of 26 coral atolls, resting on a submerged mountain range, and has a land area of 298 km2 . The human population is dense; in 2012, these islands recorded 394,451 inhabitants (Anonymous 2012). Of the 1192 islands, of which 202 are inhabited, all are small (average size 0.7 km2 , the largest 13 km2 ) and low-lying, with average elevations of not more than 1.5–2 m asl, although a few have swamps and several have small lagoons in the interior. The Maldive Archipelago lies between two other archipelagos in a north-south line; to the north linked by Minicoy (belonging to India) is the Lakshadweep (formerly La ccadive) archipelago, while to the south is the Chagos archipelago. An inventory of the islands of the Maldives, annotated with data on human population size, land use, important physical features, and former names was prepared by Maniku (1983).